Reducing CV Outcomes in Patients with AF - Hoyle, Brian (MD Conference Express, 2014)
This article discusses methods to control and reduce the level of mortality in patients with atrial fibrillation (AF). Dedicated clinics with nurse-led programs addressing of nonstroke-related mortality, ablation, and rate and rhythm control are potential strategies to explore to reduce AF-related cardiovascular outcomes.